A low thermal conductivity Ag₂Q compound, its preparation method and application

CN122647231BActive Publication Date: 2026-10-09INNER MONGOLIA UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611161140.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-09
Estimated Expiration
2046-08-03

AI Technical Summary

Technical Problem

但该方法需要数天的长时间气氛放置,增加了整体制备周期,且其核心在于除氧,并未解决致密度不足和元素化学计量比偏差

Benefits of technology

[0033] This invention features a short preparation process, high efficiency, and low energy consumption. By employing multiple discharge plasma sintering technology, it eliminates the need for pre-processing involving melting for tens of hours or high-energy ball milling for several hours, significantly shortening the entire preparation cycle. This substantial reduction in preparation time and energy consumption makes it suitable for industrial-scale mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122647231B_ABST
    Figure CN122647231B_ABST
Patent Text Reader

Abstract

The application discloses a low-thermal-conductivity Ag2Q compound and a preparation method and application thereof, and relates to the technical field of thermoelectric materials and devices. Q is at least one of S, Se or Te, the compactness of the bulk thermoelectric material is greater than or equal to 97%, and the bulk thermoelectric material is prepared from silver powder with a purity greater than or equal to 99.99% and Q (Se, Te, S) powder with a purity greater than or equal to 99.99% through multi-discharge plasma sintering. Through the process design of rapid sintering and multi-circulation, the exposure time of Se and Te in the high-temperature zone is greatly reduced, the loss of volatile elements is effectively inhibited, and the accuracy of the stoichiometric ratio of the product and the batch stability are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of thermoelectric materials and devices, specifically to a low thermal conductivity Ag2Q compound, its preparation method, and its applications. Background Technology

[0002] Thermoelectric materials are functional materials capable of directly converting heat energy into electrical energy and vice versa. Their performance is determined by the dimensionless thermoelectric figure of merit zT=S 2 σT / κ evaluation (where S is the Seebeck coefficient, σ is the electrical conductivity, T is the absolute temperature, and κ is the thermal conductivity). Ag₂Q (Q=S, Se, Te)-based thermoelectric materials, as an emerging n-type room-temperature thermoelectric material, possess advantages such as abundant elemental reserves, environmental friendliness, and excellent mechanical flexibility. In particular, due to their extraordinary deformation capacity similar to metals at room temperature, they have broad application prospects in the field of flexible wearable thermoelectric devices. However, the high carrier concentration of this material limits the Seebeck coefficient, and the Ag elemental substances precipitated during the preparation process further worsen this situation, severely restricting the stability of its thermoelectric performance and practical applications. Therefore, precise control of the stoichiometry and avoidance of elemental volatilization and impurity phase formation are key to preparing high-performance Ag₂Q bulk materials.

[0003] Currently, the traditional process for preparing Ag₂Q thermoelectric materials mainly employs a two-step method of "melting + spark plasma sintering (SPS)," which involves first preparing a precursor through high-temperature melting for over 60 hours, followed by SPS densification. This process suffers from significant drawbacks, including long cycle time, high energy consumption, easy volatilization of Se and Te leading to compositional deviations, and the introduction of harmful impurities due to prolonged high-temperature treatment. Although spark plasma sintering (SPS) technology has been introduced due to its advantages such as rapid heating, short sintering time, and effective suppression of element volatilization, a single SPS process often results in numerous microscopic defects, severely affecting the thermoelectric transport properties of the material.

[0004] To improve density and microstructure, researchers have attempted to employ multiple or cyclic sintering processes. For example, Chinese patent CN112028632A discloses a non-stoichiometric bismuth telluride-based thermoelectric material and its preparation method. This patent uses mechanical alloying combined with cyclic discharge plasma sintering (repeated heating and cooling 1-5 times). Excess Te is introduced into the eutectic liquid phase to assist grain growth and generate dislocations, thereby improving the thermoelectric figure of merit (zT value up to 1.46) of p-type bismuth telluride. However, this method is for the Bi-Sb-Te system, and this patent relies on excess Te to form the eutectic liquid phase. This strategy is not applicable to the Ag₂Q system because excess Ag or Q in Ag₂Q alters the carrier concentration, and Ag is easily precipitated, making it impossible to improve density through a liquid-phase sintering-like method. Furthermore, the raw materials in this patent require high-energy ball milling (for several hours) for mechanical alloying, which is still a multi-step process, and the problem of Se and Te volatilization remains.

[0005] Another Chinese patent, CN113161473A, discloses a method for improving the performance of p-type polycrystalline bismuth telluride materials. This method employs a thermal explosion method to rapidly synthesize a precursor, followed by placing the powder in a non-oxygen atmosphere (such as argon) for 1-5 days to remove adsorbed oxygen from the powder surface, preventing oxygen from reacting with the material and reducing carrier concentration. The material is then subjected to spark plasma sintering to obtain a high-performance material. The advantage of this method is that the atmosphere treatment repairs surface defects generated during the crushing process, thereby improving conductivity. However, this method requires several days of long atmosphere placement, increasing the overall preparation cycle. Furthermore, its core function is oxygen removal, and it does not address insufficient density or deviations in elemental stoichiometry.

[0006] Therefore, developing a process suitable for the Ag2Q system that can rapidly prepare bulk materials with high density, uniform composition, and excellent thermoelectric properties is of great practical significance. Summary of the Invention

[0007] Therefore, this invention provides a low thermal conductivity Ag₂Q compound, its preparation method, and its applications to solve the problems in the prior art. The low thermal conductivity Ag₂Q compound of this invention is actually a high Seebeck coefficient Ag₂Q bulk thermoelectric material; that is, this invention actually provides a high Seebeck coefficient Ag₂Q bulk thermoelectric material and its preparation method.

[0008] To achieve the above objectives, the present invention provides the following technical solution:

[0009] According to one aspect of the present invention, a high Seebeck coefficient Ag₂Q bulk thermoelectric material is provided, wherein Q is at least one of S, Se, or Te, and the density of the bulk thermoelectric material is ≥97%, wherein Ag₂Se, Ag₂Te, or Ag 2±y Se 1±x Ag 2±y Te 1±x The system exhibits a room temperature electrical conductivity ≥80,000 S / m, reaching a maximum of 130,000 S / m; a Seebeck coefficient ≥135 μV / K, reaching a maximum of 161 μV / K; a thermal conductivity ≤1 W / m·K; and a thermoelectric figure of merit zT of 0.6–1.0 within the temperature range of 300 K–383 K. (Ag) 2± y Se x Te 1-x The system exhibits a room temperature electrical conductivity ≥44000 S / m, reaching a maximum of 120000 S / m; a Seebeck coefficient ≥120 μV / K, reaching a maximum of 159 μV / K; a thermal conductivity ≤1 W / m·K; and a thermoelectric figure of merit zT of 0.35–0.97 within the temperature range of 300 K–383 K. (Ag) 2±y S x Te1-x The system has a room temperature electrical conductivity ≥20000 S / m, up to 90000 S / m, a Seebeck coefficient absolute value ≥85 μV / K, up to 191 μV / K, a thermal conductivity ≤1 W / m·K, and a thermoelectric figure of merit zT of 0.2-0.55 in the temperature range of 300K-383K.

[0010] Furthermore, the bulk thermoelectric material is prepared by multiple discharge plasma sintering processes using silver powder with a purity of ≥99.99% and Q powder with a purity of ≥99.99%.

[0011] Furthermore, the bulk thermoelectric material has any one of the following chemical formulas:

[0012] Ag2Se, Ag2Te;

[0013] or Ag 2±y Se 1±x Ag 2±y Te 1±x Ag 2±y S x Te 1-x Ag 2±y Se x Te 1-x , of which 0 <x<1,0<y<1。

[0014] According to another aspect of the present invention, a method for preparing the above-described high-density, low-thermal-conductivity Ag₂Q bulk thermoelectric material includes the following steps:

[0015] (1) Weigh silver powder and Q powder according to the target chemical formula ratio, wherein Q is at least one of S, Se or Te, mix them evenly and then put them into a graphite mold.

[0016] (2) Place the graphite mold containing the mixed powder in the discharge plasma sintering equipment and perform the first discharge plasma sintering under vacuum atmosphere to obtain the first sintered block.

[0017] (3) Remove the carbon paper from the surface of the first sintered block obtained in step (2) and then crush and grind it.

[0018] (4) The powder obtained in step (3) is loaded into the graphite mold again and placed in the discharge plasma sintering equipment for a second discharge plasma sintering until Ag2Q bulk thermoelectric material with a density ≥97% is obtained.

[0019] If the system contains a large amount of Te, only two SPS cycles are needed to reduce volatilization. If the system contains sulfur, multiple SPS cycles are required for thorough mixing.

[0020] Further, in step (1), the specific operation of mixing evenly is as follows: the weighed powder is placed in an agate mortar, and ethanol with a mass fraction of 95%±5% is used as a dispersant. The powder is stirred evenly in one direction for 15min~60min until the slurry is dried to obtain a uniformly mixed powder.

[0021] Furthermore, in step (1), the inner diameter of the graphite mold is 10mm~30mm.

[0022] Furthermore, in step (3), after crushing and grinding, the material is sieved with a screen mesh of 100 mesh.

[0023] Furthermore, in steps (2) and (4), the process parameters for spark plasma sintering are as follows:

[0024] Vacuum degree ≤1×10 -4 Pa;

[0025] The heating rate is 20℃ / min to 60℃ / min;

[0026] The sintering temperature is 120℃~600℃;

[0027] The axial pressure is 50MPa~70MPa;

[0028] The sintering holding time is 0 min to 30 min;

[0029] After the heat preservation period, the furnace is cooled to room temperature.

[0030] Furthermore, the sintering temperature is 120℃~600℃, and the sintering time is 2min~30min; the spark plasma sintering also includes: after the temperature rise is completed, holding at 120℃~600℃ for 0min~60min (that is, when the holding time is 0min, it means no holding is required, and the furnace is cooled).

[0031] The third aspect of the present invention provides the application of a low thermal conductivity Ag2Q compound as described above in the fabrication of thermoelectric materials and devices.

[0032] The present invention has the following advantages:

[0033] This invention features a short preparation process, high efficiency, and low energy consumption. By employing multiple discharge plasma sintering technology, it eliminates the need for pre-processing involving melting for tens of hours or high-energy ball milling for several hours, significantly shortening the entire preparation cycle. This substantial reduction in preparation time and energy consumption makes it suitable for industrial-scale mass production.

[0034] This invention significantly reduces the exposure time of Se and Te in the high-temperature zone through rapid sintering and multiple cycles, effectively suppressing the loss of volatile elements and ensuring the accuracy of the product stoichiometry and batch stability.

[0035] This invention employs a multi-sintering strategy with two or more sintering cycles, and performs crushing, grinding, and sieving processes between each sintering cycle to achieve more thorough densification of the material during subsequent sintering. The resulting bulk material achieves a density of over 97%, significantly superior to samples prepared by a single SPS cycle, effectively reducing the adverse effects of microscopic defects on thermoelectric transport properties.

[0036] The Ag₂Q bulk thermoelectric material prepared by this invention exhibits good performance in the near-room temperature range of 300K~383K, producing Ag₂Se, Ag₂Te, and Ag₂Se. 2±y Se 1±x Ag 2±y Te 1±x The system exhibits a room temperature electrical conductivity ≥80,000 S / m, reaching a maximum of 130,000 S / m; a Seebeck coefficient ≥135 μV / K, reaching a maximum of 161 μV / K; a thermal conductivity ≤1 W / m·K; and a thermoelectric figure of merit zT of 0.6–1.0 within the temperature range of 300 K–383 K. (Ag) 2±y Se x Te 1-x The system exhibits a room temperature electrical conductivity ≥44000 S / m, reaching a maximum of 120000 S / m; a Seebeck coefficient ≥120 μV / K, reaching a maximum of 159 μV / K; a thermal conductivity ≤1 W / m·K; and a thermoelectric figure of merit zT of 0.25–0.97 within the temperature range of 300 K–383 K. (Ag) 2±y S x Te 1-x The system exhibits a room temperature electrical conductivity ≥20000 S / m, reaching a maximum of 90000 S / m; a Seebeck coefficient ≥85 μV / K, reaching a maximum of 191 μV / K; and a thermal conductivity ≤1 W / m·K. Its thermoelectric figure of merit (zT) is 0.2-0.55 within the temperature range of 300 K-383 K. The Ag₂Q bulk thermoelectric material prepared by this invention demonstrates high reproducibility, combining high electrical transport performance with low thermal conductivity, achieving an overall thermoelectric performance at an advanced level compared to similar materials.

[0037] This invention requires only simple mixing of raw material powders before direct discharge plasma sintering. The process is concise, easy to operate, requires minimal equipment, and offers good repeatability. The bulk material prepared by this invention exhibits excellent microstructural stability, high phase purity, and few harmful impurities, which helps ensure the performance stability and service life of thermoelectric devices during actual operation. Attached Figure Description

[0038] To more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are merely exemplary, and those skilled in the art can derive other embodiments based on the provided drawings without creative effort.

[0039] The structures, proportions, sizes, etc. illustrated in this specification are only for the purpose of assisting those skilled in the art in understanding and reading the content disclosed herein, and are not intended to limit the conditions under which the present invention can be implemented. Therefore, they have no substantial technical significance. Any modifications to the structure, changes in the proportions, or adjustments to the size, without affecting the effects and objectives that the present invention can produce, should still fall within the scope of the technical content disclosed in the present invention.

[0040] Figure 1 Phase analysis diagrams of Ag2Q bulk thermoelectric materials prepared according to different embodiments of the present invention; wherein, Figure 1 (a) is the phase analysis diagram of Example 1; Figure 1 (b) is the phase analysis diagram of Example 2; Figure 1 (c) is the phase analysis diagram of Example 3; Figure 1 (d) is the phase analysis diagram of Example 4; Figure 1 (e) is the phase analysis diagram of Example 5;

[0041] Figure 2 This is a comparison diagram of the thermoelectric transport properties of Ag2Q bulk thermoelectric materials prepared in different embodiments and comparative examples of the present invention; wherein, Figure 2 (a) Seebeck coefficients for Examples 1-5; Figure 2 (b) represents the power factor for Examples 1-5; Figure 2 (c) represents the thermal conductivity of Examples 1-5; Figure 2 (d) represents the lattice thermal conductivity of Examples 1-5; Figure 2 (e) represents the zT values ​​for Examples 1-5; Figure 2 (f) represents the Seebeck coefficients for comparative examples 1-7; Figure 2 (g) represents the power factor of comparative examples 1-7; Figure 2 (h) represents the thermal conductivity of comparative examples 1-7; Figure 2 (i) represents the lattice thermal conductivity of comparative examples 1-7; Figure 2 (j) represents the zT value of comparative examples 1-7;

[0042] Figure 3 Comparison of SEM microstructure of Ag2Q bulk thermoelectric materials prepared in Example 1 and Comparative Example 1, which are provided for Test Example 6 of the present invention. Detailed Implementation

[0043] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0044] Unless otherwise specified in the embodiments of this invention, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all commercially available products; different manufacturers and models of raw materials do not affect the implementation of the technical solution or the achievement of the technical effect of this invention.

[0045] Example 1 This embodiment provides a method for preparing Ag₂Se bulk thermoelectric material, specifically including the following steps:

[0046] (1) Raw material ratio and mixing: Take Ag powder and Se powder with a purity ≥99.99% respectively, and weigh them according to the atomic ratio of Ag to Se in the chemical formula Ag2Se (2:1). Place the weighed raw materials in an agate mortar, use 99% ethanol as a dispersant, and stir evenly in one direction for 30 minutes until the slurry is dry to obtain a uniformly mixed powder.

[0047] (2) First discharge plasma sintering: The mixed powder obtained in step (1) is loaded into a graphite mold with an inner diameter of 15 mm and placed in a discharge plasma sintering equipment. The mixture is sintered under a vacuum degree ≤ 1×10 -4 Under a vacuum atmosphere of Pa, the temperature was increased to 280°C at a heating rate of 40°C / min, while an axial pressure of 55 MPa was applied, and sintering was carried out for 7 min. After sintering, the furnace was cooled to room temperature and demolded to obtain the first sintered block.

[0048] (3) Crushing and sieving: Remove the graphite paper (carbon paper) on the surface of the initial sintered block obtained in step (2), crush and grind it, and sieve it using a 100-mesh sieve.

[0049] (4) Second discharge plasma sintering: The powder obtained in step (3) is loaded into the graphite mold again and subjected to a second discharge plasma sintering under the same process parameters as in step (2).

[0050] (5) Repeat steps (3) and (4) once (i.e., perform three discharge plasma sintering processes in total) to obtain high-density Ag2Se bulk thermoelectric material.

[0051] The phase analysis diagram of the Ag2Se bulk thermoelectric material prepared in this embodiment is shown below. Figure 1 As shown in (a), the density is 98.2%, the Seebeck coefficient at room temperature is -158 μV / K, the thermal conductivity is as low as 0.94 W / m·K, and the thermoelectric figure of merit zT is 0.82~0.92 in the temperature range of 300K~383K.

[0052] Example 2 This embodiment provides a method for preparing Ag2Te bulk thermoelectric material, which specifically includes the following steps:

[0053] (1) Raw material ratio and mixing: Take Ag powder and Te powder with a purity ≥99.99% respectively, and weigh them according to the atomic ratio of Ag to Te in the chemical formula Ag2Te (2:1). Place the weighed raw materials in an agate mortar, use 99% ethanol as a dispersant, and stir evenly in one direction for 45 minutes until the slurry is dry to obtain a uniformly mixed powder.

[0054] (2) First discharge plasma sintering: The mixed powder obtained in step (1) is loaded into a graphite mold with an inner diameter of 20 mm and placed in a discharge plasma sintering equipment. The mixture is sintered under a vacuum degree ≤ 1×10 -4 Under a vacuum atmosphere of Pa, the temperature was increased to 550°C at a heating rate of 50°C / min, while an axial pressure of 55 MPa was applied, and sintering was carried out for 11 min. After sintering, the furnace was cooled to room temperature and demolded to obtain the first sintered block.

[0055] (3) Crushing and sieving: Remove the carbon paper from the surface of the initial sintered block obtained in step (2), crush and grind it, and sieve it using a 100-mesh sieve.

[0056] (4) Second discharge plasma sintering: The powder obtained in step (3) is loaded into the graphite mold again, and a second discharge plasma sintering is performed under the same process parameters as in step (2) to obtain high-density Ag2Te bulk thermoelectric material.

[0057] The phase analysis diagram of the Ag2Te bulk thermoelectric material prepared in this embodiment is shown below. Figure 1 As shown in (b), the density is 97%, the Seebeck coefficient at near room temperature is -135 μV / K, the thermal conductivity is as low as 0.92 W / m·K, and the thermoelectric figure of merit zT is 0.55 in the temperature range of 300 K to 383 K.

[0058] Example 3 This embodiment provides an Ag2Se 0.9 Te 0.1 The preparation method of solid solution bulk thermoelectric materials specifically includes the following steps:

[0059] (1) Raw material ratio and mixing: Take Ag powder, Se powder and Te powder with a purity ≥99.99% respectively, and mix them according to Ag2Se 0.9 Te 0.1 Weigh the raw materials according to the atomic ratio (Ag:Se:Te=2:0.9:0.1) in the chemical formula. Place the weighed raw materials in an agate mortar, use 99% ethanol as a dispersant, and stir evenly in one direction for 60 minutes with a grinding rod until the slurry is dry to obtain a uniformly mixed powder.

[0060] (2) First discharge plasma sintering: The mixed powder obtained in step (1) is loaded into a graphite mold with an inner diameter of 15 mm and placed in a discharge plasma sintering equipment. The mixture is sintered under a vacuum degree ≤ 1×10 -4 Under a vacuum atmosphere of Pa, the temperature was increased to 280°C at a heating rate of 70°C / min, while an axial pressure of 60 MPa was applied, and sintering was carried out for 4 min. After sintering, the furnace was cooled to room temperature and demolded to obtain the first sintered block.

[0061] (3) Crushing and sieving: Remove the carbon paper from the surface of the initial sintered block obtained in step (2), crush and grind it, and sieve it using a 100-mesh sieve.

[0062] (4) Second spark plasma sintering: The powder obtained in step (3) is loaded back into the graphite mold and subjected to a second spark plasma sintering under the same process parameters as in step (2) to obtain high-density Ag2Se. 0.9 Te 0.1 Bulk thermoelectric materials.

[0063] The Ag2Se prepared in this embodiment 0.9 Te 0.1 Phase analysis diagram of bulk thermoelectric material as shown in the figure Figure 1 As shown in (c), the density is 97.8%, the Seebeck coefficient at room temperature is -156 μV / K, the thermal conductivity can reach 0.91 W / m·K, and the thermoelectric figure of merit zT is 0.91~0.97 in the temperature range of 300K~383K.

[0064] Example 4 This embodiment provides an Ag2S 0.3 Te 0.7 The preparation method of bulk thermoelectric materials specifically includes the following steps:

[0065] (1) Raw material ratio and mixing: Take Ag powder, S powder and Te powder with a purity ≥99.99% respectively, and mix them according to Ag2S 0.3 Te 0.7Weigh the raw materials according to the atomic ratio (Ag:S:Te=2:0.3:0.7) in the chemical formula. Place the weighed raw materials in an agate mortar, use 99% ethanol as a dispersant, and stir evenly in one direction for 50 minutes until the slurry is dry to obtain a uniformly mixed powder.

[0066] (2) First discharge plasma sintering: The mixed powder obtained in step (1) is loaded into a graphite mold with an inner diameter of 18 mm and placed in a discharge plasma sintering equipment. The mixture is sintered under a vacuum degree ≤ 1×10 -4 Under a vacuum atmosphere of Pa, the temperature was increased to 600℃ at a heating rate of 60℃ / min, while an axial pressure of 70MPa was applied, and sintering was carried out for 10 minutes. After sintering, the furnace was cooled to room temperature and demolded to obtain the first sintered block.

[0067] (3) Crushing and sieving: Remove the carbon paper from the surface of the initial sintered block obtained in step (2), crush and grind it, and sieve it using a 100-mesh sieve.

[0068] (4) Second discharge plasma sintering: The powder obtained in step (3) is loaded into the graphite mold again and subjected to a second discharge plasma sintering under the same process parameters as in step (2).

[0069] (5) Repeat steps (3) and (4) twice (i.e., perform a total of four discharge plasma sintering processes) to obtain high-density Ag2S. 0.3 Te 0.7 Bulk thermoelectric materials.

[0070] The Ag2S prepared in this embodiment 0.3 Te 0.7 Phase analysis diagram of bulk thermoelectric material as shown in the figure Figure 1 As shown in (d), the density is 98.0%, the Seebeck coefficient near room temperature can reach -101 μV / K, the thermal conductivity is as low as 0.65 W / m·K, and the thermoelectric figure of merit zT is 0.29~0.38 in the temperature range of 300K~383K.

[0071] Example 5 This embodiment provides an Ag 2.001 The preparation method of Se bulk thermoelectric material specifically includes the following steps:

[0072] (1) Raw material ratio and mixing: Take Ag powder and Se powder with a purity ≥99.99% respectively, and mix them according to Ag 2.001 Weigh the raw materials according to the atomic ratio of Se in the chemical formula (Ag:Se=2.001:1). Place the weighed raw materials in an agate mortar, use 99% ethanol as a dispersant, and stir evenly in one direction for 20 minutes with a grinding rod until the slurry is dry to obtain a uniformly mixed powder.

[0073] (2) First discharge plasma sintering: The mixed powder obtained in step (1) is loaded into a graphite mold with an inner diameter of 12 mm and placed in a discharge plasma sintering equipment. The vacuum degree is ≤1×10 -4 Under a vacuum atmosphere of Pa, the sintering parameters were the same as those for Ag2Se; after sintering, the furnace was cooled to room temperature and demolded to obtain the first sintered block.

[0074] (3) Crushing and sieving: Remove the carbon paper from the surface of the initial sintered block obtained in step (2), crush and grind it, and sieve it using a 100-mesh sieve.

[0075] (4) Second discharge plasma sintering: The powder obtained in step (3) is loaded into the graphite mold again and subjected to a second discharge plasma sintering under the same process parameters as in step (2).

[0076] (5) Repeat steps (3) and (4) once (i.e., perform three discharge plasma sintering processes in total) to obtain high-density Ag. 2.001 Se bulk thermoelectric materials.

[0077] The Ag prepared in this embodiment 2.001 Phase analysis diagram of Se bulk thermoelectric material is shown below. Figure 1 As shown in (e), the density is 97.5%, the Seebeck coefficient at room temperature is -161 μV / K, the thermal conductivity is as low as 0.98 W / m·K, and the thermoelectric figure of merit zT is 0.83~1.00 in the temperature range of 300K~383K.

[0078] Comparative Example 1 This comparative example provides a method for preparing Ag₂Se bulk thermoelectric materials using a traditional two-step method of "melting + spark plasma sintering", specifically including the following steps:

[0079] (1) Weigh Ag powder and Se powder with a purity ≥99.99% according to the atomic ratio of Ag to Se in the chemical formula Ag2Se (2:1). Mix them in a mortar for about 60 minutes. After mixing evenly, place them in a quartz tube and evacuate to a vacuum of ≤1×10⁻⁶. -4 After Pa, seal the tube.

[0080] (2) The sealed quartz tube is placed in a muffle furnace and heated to 1273K according to the program. It is held for 12 hours and then annealed at 723K for 72 hours. After that, it is cooled to room temperature with the furnace. The quartz tube is broken and Ag2Se ingot is taken out to obtain Ag2Se ingot.

[0081] (3) The obtained Ag2Se ingot is crushed and ground, and then sieved through a sieve to obtain Ag2Se powder.

[0082] (4) The powder obtained in step (3) is loaded into a graphite mold and placed in a spark plasma sintering equipment. It is sintered in a vacuum atmosphere. After sintering, it is cooled to room temperature with the furnace and demolded to obtain Ag2Se bulk thermoelectric material.

[0083] The Ag2Se bulk thermoelectric material prepared in this comparative example has a density of >97.2%, a Seebeck coefficient of only -119 μV / K near room temperature, and a thermoelectric figure of merit zT of 0.43~0.60 in the temperature range of 300K~383K.

[0084] Comparative Example 2 This comparative example provides a method for preparing Ag2Te bulk thermoelectric materials using a traditional two-step method of "melting + spark plasma sintering", specifically including the following steps:

[0085] (1) Weigh Ag powder and Te powder with a purity ≥99.99% according to the atomic ratio of Ag to Te in the chemical formula Ag2Te (2:1). Mix them in a mortar for about 45 minutes. After mixing evenly, place them in a quartz tube and evacuate to a vacuum of ≤1×10⁻⁶. -4 After Pa, seal the tube.

[0086] (2) Place the sealed quartz tube in a muffle furnace, heat it to 1273K according to the program, hold it for 10 hours, and then cool it to room temperature with the furnace. Break the quartz tube and take out the Ag2Te ingot to obtain the Ag2Te ingot.

[0087] (3) The obtained Ag2Te ingot is crushed and ground, and then sieved through a sieve to obtain Ag2Te powder.

[0088] (4) The powder obtained in step (3) is loaded into a graphite mold and placed in a spark plasma sintering equipment. It is sintered in a vacuum atmosphere. After sintering, it is cooled to room temperature with the furnace and demolded to obtain Ag2Te bulk thermoelectric material.

[0089] The Ag2Te bulk thermoelectric material prepared in this comparative example has a density of >97.0%, a Seebeck coefficient of only -94 μV / K near room temperature, and a thermoelectric figure of merit zT of 0.47~0.52 in the temperature range of 300K~383K.

[0090] Comparative Example 3 This comparative example provides a method for preparing Ag₂Se using the traditional melt annealing method. x Te 1-x The method for using bulk thermoelectric materials specifically includes the following steps:

[0091] (1) According to Ag2Se x Te 1-x The atomic ratios in the chemical formula were determined by weighing Ag powder, Se powder, and Te powder with a purity ≥ 99.99%, and synthesizing a ternary Ag₂Se using a simplified wet mechanical alloying process.1-x Tex (x=0.1, 0.2, 0.3, 0.4 and 0.5) powder.

[0092] (2) The prepared powder is placed in a quartz tube and evacuated to a vacuum of ≤1×10⁻⁶. -4 After Pa, seal the tube.

[0093] (3) Place the sealed quartz tube in a muffle furnace, heat it to 673K ​​according to the program, hold it for 10h, then heat it to 1273K and hold it for 10h, then cool it down to 393K within 30h, hold it for 12h, and then cool it down to room temperature with the furnace. Take out the ingot from the broken quartz tube and cut it into the required shape and size for characterization analysis.

[0094] The Ag2Se prepared in this comparative example 0.9 Te 0.1 The bulk thermoelectric material has a density of 93.79%, but its Seebeck coefficient near room temperature is only -136 μV / K, and its thermoelectric figure of merit zT is 0.68-0.79 in the temperature range of 300K~383K.

[0095] Comparative Example 4 This comparative example provides a method for preparing Ag2S using the traditional melt annealing method. x Te 1-x The method for using bulk thermoelectric materials specifically includes the following steps:

[0096] (1) According to Ag2S x Te 1-x Weigh out Ag powder, S powder and Te powder with a purity ≥ 99.99% in a mortar, mix them in a mortar for more than 60 minutes until uniform, then transfer them to a quartz tube with a thin carbon film coated on the inner wall and seal it under vacuum conditions.

[0097] (2) Place the quartz tube in the furnace, heat it to 1323K within 15 hours and maintain that temperature for 48 hours, then cool it to 823K within 34 hours. After annealing at this temperature for 3 days, lower the furnace temperature to 393K and maintain it for 10 hours, and finally cool it to room temperature.

[0098] (3) The resulting ingot has extremely high density and no obvious internal pores, and can be directly cut into the required shape and size for characterization analysis.

[0099] The Ag2S prepared in this comparative example 0.3 Te 0.7 The bulk thermoelectric material has a density of >97.0%, but its Seebeck coefficient near room temperature is -136μV / K, and its thermoelectric figure of merit zT is 0.24-0.35 in the temperature range of 300K~383K.

[0100] Comparative Example 5 This comparative example provides a method for preparing Ag₂Se bulk thermoelectric materials using single-discharge plasma sintering, specifically including the following steps:

[0101] (1) The raw materials were proportioned and mixed in the same way as in Example 1.

[0102] (2) The mixed powder is loaded into a graphite mold and placed in a spark plasma sintering apparatus, with a vacuum degree ≤1×10 - 4 Under a vacuum atmosphere of Pa, the temperature was raised to 400℃ at heating rates of 150, 200, and 250℃ / min, respectively. After sintering, the material was cooled to room temperature in the furnace and demolded to obtain Ag2Se bulk thermoelectric material (only one SPS was performed, without crushing and re-firing).

[0103] The Ag2Se bulk thermoelectric material prepared in this comparative example has a density of nearly 92.46%, and its room temperature Seebeck coefficient ranges from a maximum of -151 μV / K to a minimum of -81 μV / K. Its electrical transport properties exhibit huge fluctuations and low repeatability, with zT values ​​of only 0.60-0.79.

[0104] Comparative Example 6 This comparative example provides a method for preparing Ag2Te bulk thermoelectric materials using single-discharge plasma sintering, specifically including the following steps:

[0105] (1) The raw materials were proportioned and mixed in the same way as in Example 2.

[0106] (2) The mixed powder is loaded into a graphite mold and placed in a spark plasma sintering apparatus, with a vacuum degree ≤1×10 - 4 Under a vacuum atmosphere of Pa, the temperature was increased to 350°C at a heating rate of 50°C / min, while an axial pressure of 60 MPa was applied, and sintering was carried out for 15 min. After sintering, the material was cooled to room temperature in the furnace and demolded to obtain Ag2Te bulk thermoelectric material (only one SPS was performed, without crushing and re-firing).

[0107] Although the Ag2Te bulk thermoelectric material prepared in this comparative example has a density of 98.0%, its Seebeck coefficient is only -124.5 μV / K and its thermoelectric figure of merit zT is only 0.40~0.58 in the temperature range of 300K~383K.

[0108] Comparative Example 7 This comparative example provides a method for preparing Ag₂Se bulk thermoelectric materials using single-discharge plasma sintering, specifically including the following steps:

[0109] (1) Raw material ratio and ball milling

[0110] According to the atomic ratio of Ag to Se in the chemical formula Ag2Se (2:1), Ag powder and Se powder with a purity ≥99.99% were weighed. The raw materials were placed in a stainless steel ball mill jar with a mass ratio of grinding balls to raw materials of 20:1. The ball mill jar was filled with an argon protective atmosphere and ball milled in a planetary ball mill at a speed of 383 r / min for 6 hours to obtain alloyed powder.

[0111] (2) First discharge plasma sintering

[0112] The powder obtained from ball milling was loaded into a graphite mold, compacted, and then placed in a spark plasma sintering furnace. The furnace was heated to 420°C within 7 minutes at a vacuum of 5 Pa and a longitudinal pressure of 50 MPa, followed by cyclic sintering.

[0113] (3) Circulating heating and cooling treatment

[0114] Each cycle consists of a 2-minute heating phase from 420°C to 470°C, followed by a 3-minute cooling phase from 470°C to 420°C. This heating and cooling cycle is repeated 4 times.

[0115] (4) Cooling

[0116] After the cycle is completed, the material is cooled to room temperature in the furnace and then demolded to obtain Ag2Se bulk thermoelectric material.

[0117] The sample density was only 83.5%, while the density of thermoelectric materials usually needs to reach 94% or higher.

[0118] Test Example 1 Density Test: The density of the sample is determined using Archimedes' principle. The test principle is as follows: the buoyant force on the sample in the liquid is equal to the weight of the displaced liquid. Before the test, the sample needs to be gently polished to remove surface impurities, ultrasonically cleaned, and then the surface moisture absorbed with lint-free paper to avoid errors affecting the experimental data. For numerical accuracy, three weighings are performed, and the final average value is taken. The density is calculated using the formula ρ = ρ_a - ρ_b. L +A / (AB)*(ρ0-ρ L ), where A is the mass of the sample in air (g); B is the mass of the sample in the liquid (g). The measured density ρ (the theoretical density of Ag₂Se is 8.25 g / cm³) was determined. 3 The theoretical density of Ag₂Te is 8.41 g / cm³. 3 ).

[0119] The test results are shown in Table 1.

[0120] Table 1. Density test results of each embodiment and comparative example. Example 1 98.2 Example 2 97.0 Example 3 97.8 Example 4 98.0 Example 5 97.5 Comparative Example 1 97.2 Comparative Example 2 97.1 Comparative Example 3 93.8 Comparative Example 4 97.5 Comparative Example 5 92.5 Comparative Example 6 98.0 Comparative Example 7 83.5

[0121] As shown in Table 1, the Ag2Q bulk thermoelectric materials prepared in Examples 1-5 of the present invention all have a density of over 97%, indicating that the present invention effectively improves the density of bulk materials through multiple discharge plasma sintering combined with intermediate crushing and sieving.

[0122] Test Example 2 Seebeck test: The bulk thermoelectric materials prepared in each embodiment were subjected to Seebeck tests using an LSR-3 Seebeck coefficient & resistivity tester. The tests were conducted under a helium atmosphere, with a temperature range of 323K~383K. The samples were processed into discs (approximately 15mm×15mm×2mm in size), and the sample surfaces were polished before testing to ensure good electrical contact.

[0123] Power factor calculation: Based on the test results of Test Example 2, according to the formula PF=S 2 σ calculates the power factor of each embodiment and comparative example at near room temperature (323 K).

[0124] The test results are shown in Table 2 (data at near room temperature, 323K).

[0125] Table 2 Seebeck coefficient and power factor at near room temperature (323 K) for each embodiment and comparative example. Example 1 -158 2.38 Example 2 -135 1.59 Example 3 -156 2.58 Example 4 -84 0.60 Example 5 -161 2.32 Comparative Example 1 -119 2.96 Comparative Example 2 -90 1.45 Comparative Example 3 -136 1.70 Comparative Example 4 -65 0.50 Comparative Example 5 -151 2.40 Comparative Example 6 -124 0.68 Comparative Example 7 -112 0.69

[0126] Example 1 was Ag₂Se, Example 2 was Ag₂Te, and Example 3 was Ag₂Se. 0.9 Te 0.1 Example 4 is Ag2S 0.3 Te 0.7 Examples 1, 2, 3, and 4 correspond to different preparation methods for the same sample, with Example 5 using Ag. 2.001 Examples 5, 6, and 7 represent single-cycle SPS preparation of Ag₂Se, Ag₂Te, and cyclic preparation of Ag₂Se, respectively. As shown in Table 2, under the same system, the absolute values ​​of the room-temperature Seebeck coefficients of the Ag₂Q bulk thermoelectric materials prepared in the embodiments of the present invention are significantly better than those of the comparative examples, indicating better electrical transport performance. However, the quality of thermoelectric materials is evaluated by the zT value. The parameters of the zT value have a strong coupling relationship, so it cannot be evaluated by a single Seebeck coefficient. Therefore, we conducted thermal transport tests.

[0127] Test Example 3 Thermal conductivity testing: The thermal diffusivity of the bulk thermoelectric materials in each embodiment was tested using an LFA-457 laser thermal conductivity meter. Samples were processed into circular discs with a diameter of 12.7 ± 0.2 mm and a thickness of approximately 2 mm, with double-sided carbon spraying to improve surface light absorption. The test temperature range was 323 K to 383 K, with three tests conducted at each temperature point and the average value taken. Thermal conductivity κ was calculated using the formula κ = α·ρ·Cp, where α is the thermal diffusivity, ρ is the sample density, and Cp is the specific heat capacity. The total thermal conductivity was subtracted from the electronic thermal conductivity κe (calculated using the Wiedemann-Franz law κe = L·σ·T, where L is the Lorentz constant, obtained through L = [1.5 + exp(-|S| / 116)] × 10). -8 The lattice thermal conductivity κL is calculated.

[0128] The test results are shown in Table 3 (data at near room temperature, 323K).

[0129] Table 3 Thermal conductivity of each embodiment and comparative example Example 1 0.94 0.28 Example 2 0.99 0.32 Example 3 0.91 0.25 Example 4 0.65 0.30 Example 5 0.95 0.29 Comparative Example 1 1.43 0.40 Comparative Example 2 0.92 0.49 Comparative Example 3 0.82 0.33 Comparative Example 4 0.59 0.02 Comparative Example 5 1.08 0.55 Comparative Example 6 1.02 0.79 Comparative Example 7 1.32 0.38

[0130] From Table 3 and Figure 2 It can be seen that the Ag2Q bulk thermoelectric materials prepared in Examples 1-5 of the present invention have low total thermal conductivity (0.65~0.99 W·m). -1 ·K -1 ) and lattice thermal conductivity (0.25~0.32 W·m) -1 ·K -1 This indicates that multiple discharge plasma sintering is beneficial for introducing phonon scattering centers and reducing lattice thermal conductivity.

[0131] Test Example 4 Thermoelectric figure of merit zT test and calculation: Based on the test results of test examples 2 and 3, zT is calculated using the formula zT = S 2 The thermoelectric figure of merit zT of each embodiment and comparative example at different temperatures was calculated using σT / κ. Where S is the Seebeck coefficient, σ is the electrical conductivity, T is the absolute temperature, and κ is the total thermal conductivity. The test and calculation results are shown in Table 4.

[0132] Table 4. Thermoelectric figure of merit zT (300K~383K) of each embodiment and comparative example Example 1 0.821 0.893 0.925 0.918 Example 2 0.514 0.526 0.537 0.551 Example 3 0.912 0.931 0.971 0.947 Example 4 0.296 0.316 0.346 0.385 Example 5 0.620 0.520 0.530 0.470 Comparative Example 1 0.608 0.578 0.516 0.439 Comparative Example 2 0.477 0.489 0.520 0.528 Comparative Example 3 0.687 0.725 0.7624 0.793 Comparative Example 4 0.246 0.264 0.306 0.351 Comparative Example 5 0.760 0.790 0.720 0.740 Comparative Example 6 0.220 0.180 0.140 0.080 Comparative Example 7 0.170 0.180 0.190 0.190

[0133] As shown in Table 4, the Ag2Q bulk thermoelectric materials prepared in Examples 1-5 of this invention all achieved thermoelectric figures of merit (zT) of 0.29-0.91 within a temperature range of 300K-383K, meeting the technical specifications of this invention and significantly superior to comparative examples 1-7 (zT only 0.24-0.79). Example 3 (Ag2Se) 0.9 Te 0.1The solid solution (with two SPS processes) exhibited the best thermoelectric performance, with zT reaching 0.97 at 363 K, indicating that the solid solution strategy combined with multiple SPS processes can further optimize thermoelectric performance. Example 4, however, used Ag2S... x Te 1-x The system exhibits reduced thermoelectric properties due to sulfur doping but superior mechanical properties. However, compared to comparative examples, the method of this invention still achieves a higher thermoelectric figure of merit. While the thermoelectric properties and achievable thermoelectric figures of merit vary among systems, the sample prepared by the method of this invention effectively improves the Seebeck coefficient and reduces total thermal conductivity compared to current conventional preparation methods, achieving a good thermoelectric figure of merit while maintaining high density, thus meeting the requirements of this invention.

[0134] Test Example 5: Phase Analysis (XRD) Phase analysis of the bulk thermoelectric materials prepared in each example and comparative example was performed using an X-ray diffractometer (XRD, Bruker D8 Advance, Germany, Cu Kα radiation, λ=1.5406Å). The test conditions were: operating voltage 40kV, operating current 40mA, scanning range 2θ=20°~80°, scanning step size 0.02°, and scanning speed 2° / min.

[0135] Test results show that: The XRD diffraction peaks of the Ag2Q bulk thermoelectric materials prepared in Examples 1-5 of this invention are in good agreement with the standard cards (Ag2SePDF#24-1041, Ag2TePDF#34-0142), and no obvious Ag or Q impurity peaks appear, indicating that pure phase Ag2Q compounds were successfully obtained through multiple discharge plasma sintering.

[0136] Test Example 6: Microscopic Morphology Analysis (SEM) The microstructure of the bulk thermoelectric materials prepared in each embodiment and comparative example was observed using field emission scanning electron microscopy (FE-SEM, Zeiss Ultra Plus, Germany).

[0137] SEM images of Example 1 and Comparative Example 1 are shown below. Figure 3 As shown, by Figure 3 It can be seen that the sample of Example 1 is more uniform overall, with a denser structure, a smoother surface, fewer macroscopic pores, and a significant reduction in large-sized black pores. Parallel polishing scratches are very obvious, indicating that the surface in this area is relatively smooth, and the observed marks are mainly mechanical polishing traces. Comparative Example 1 (conventional melting + SPS method) has a large number and larger pores, poor surface uniformity, and black areas are mostly irregular blocks, with some showing aggregation. The surface undulations are more obvious, with locally visible bright white particles, and the polishing scratches are more varied in direction and frequently interrupted by pores.

[0138] Although the present invention has been described in detail above with general descriptions and specific embodiments, modifications or improvements can be made to it, which will be obvious to those skilled in the art. Therefore, all such modifications or improvements made without departing from the spirit of the present invention fall within the scope of protection claimed by the present invention.

Claims

1. A low thermal conductivity Ag₂Q compound, characterized in that, The compound is a high Seebeck coefficient Ag2Q bulk thermoelectric material, wherein Q is at least one of S, Se or Te, the bulk thermoelectric material has a density ≥97%, and the bulk thermoelectric material is prepared by multiple discharge plasma sintering processes of silver powder with a purity ≥99.99% and Q powder with a purity ≥99.99%. The preparation method of the Ag2Q compound with low thermal conductivity includes the following steps: (1) Weigh silver powder and Q powder according to the target chemical formula ratio, wherein Q is at least one of S, Se or Te, mix them evenly and then put them into a graphite mold. (2) Place the graphite mold containing the mixed powder in the discharge plasma sintering equipment and perform the first discharge plasma sintering under vacuum atmosphere to obtain the first sintered block. (3) Remove the carbon paper from the surface of the first sintered block obtained in step (2) and then crush and grind it. (4) The powder obtained in step (3) is loaded into the graphite mold again and placed in the discharge plasma sintering equipment for a second discharge plasma sintering. (5) Repeat steps (3) and (4) until Ag2Q bulk thermoelectric material with a density ≥97% is obtained.

2. The low thermal conductivity Ag₂Q compound according to claim 1, characterized in that, The bulk thermoelectric material has any one of the following chemical formulas: Ag2Se, Ag2Te; Or Ag 2±y Yes 1±x 、Ag 2±y You 1±x 、Ag 2±y S x You 1-x 、Ag 2±y Yes x You 1-x , among which 0 <x<1,0<y<1。 3. The low thermal conductivity Ag₂Q compound according to claim 2, characterized in that, The Ag2Se, Ag2Te, Ag 2± y Se 1±x Ag 2±y Te 1±x The system exhibits a room temperature electrical conductivity ≥80,000 S / m, up to a maximum of 130,000 S / m; a Seebeck coefficient ≥135 μV / K, up to a maximum of 161 μV / K; a thermal conductivity ≤1 W / m·K; and a thermoelectric figure of merit zT of 0.6–1.0 in the temperature range of 300 K–383 K. (Ag) 2±y Se x Te 1-x The system exhibits a room temperature electrical conductivity ≥44000 S / m, reaching a maximum of 120000 S / m; a Seebeck coefficient ≥120 μV / K, reaching a maximum of 159 μV / K; a thermal conductivity ≤1 W / m·K; and a thermoelectric figure of merit zT of 0.35–0.97 in the temperature range of 300 K–383 K. (Ag) 2±y S x Te 1-x The system has a room temperature electrical conductivity ≥20000 S / m, up to 90000 S / m, a Seebeck coefficient absolute value ≥85 μV / K, up to 191 μV / K, a thermal conductivity ≤1 W / m·K, and a thermoelectric figure of merit zT of 0.2-0.55 in the temperature range of 300K-383K.

4. The low thermal conductivity Ag₂Q compound according to claim 1, characterized in that, In step (1), the specific operation of uniform mixing is as follows: the weighed powder is placed in an agate mortar, and ethanol with a mass fraction of 95%±5% is used as a dispersant. The powder is stirred evenly in one direction for 15min~60min until the slurry is dried to obtain a uniformly mixed powder.

5. The low thermal conductivity Ag₂Q compound according to claim 1, characterized in that, In step (1), the inner diameter of the graphite mold is 10mm~30mm.

6. The low thermal conductivity Ag₂Q compound according to claim 1, characterized in that, In step (3), after crushing and grinding, the material is sieved with a mesh size of 100.

7. The low thermal conductivity Ag₂Q compound according to any one of claims 1-6, characterized in that, In steps (2) and (4), the process parameters for spark plasma sintering are as follows: Vacuum degree ≤1×10 -4 Pa; The heating rate is 20℃ / min to 60℃ / min; The sintering temperature is 120℃~600℃; The axial pressure is 50MPa~70MPa; The sintering holding time is 0 min to 30 min; After the heat preservation period, the furnace is cooled to room temperature.

8. The application of a low thermal conductivity Ag2Q compound as described in any one of claims 1-7 in the fabrication of thermoelectric materials and devices.

Citation Information

Patent Citations

  • Non-stoichiometric bismuth telluride-based thermoelectric material and preparation method thereof

    CN112028632A

  • Method for improving performance of p-type polycrystalline bismuth telluride material and preparation method

    CN113161473A

  • Ag2Se-based thermoelectric material and preparation method thereof

    CN120757078A

  • Preparation method capable of improving thermoelectric properties of tin(II) selenide-based material via combination of composition regulation and mesoscopically ordered regulation

    WO2026036565A1